Health hazard of the increased widespread use of new technologies by children and young people in northern Italy - Fubini, Enrica; Micheletti Cremasco, Margherita; Toscano, Elisabetta; Busceti, Filomena; Laporta, Stefania; Ladisa, Giorgia (SJWEH Supplements, 2007)
' ' OBJECTIVES ': 'This study analyzed the relationship children have with technological devices and took into account the physical, psychological and behavioral effects of the excessive use of new technology in comparison with the short amount of time spent in practicing sports. ' ' METHODS ': 'Altogether 585 students completed a questionnaire on the use of video display terminals (VDT), television (TV) sets and playstations, and on their health, following the use of such devices. A subsample completed a questionnaire on sports activities. ' ' RESULTS ': 'The main result was that the total average time spent in front of a playstation, VDT, and TV was very high, and a large percentage of children complain of eyestrain or musculoskeletal disorders after the use of VDT or playstations. In addition, most of the young people surveyed tended to practice very little sport. ' ' CONCLUSIONS ': 'The authors concluded that it is very important to pay more attention to the quality of children’s leisure-time activities in order to stimulate active and healthy lifestyles.
Keywords: child; children; developmental age; health hazard; Italy; new technologies; sedentary lifestyle; sport; technological device; young people